Structural characteristics of camel-bone gelatin by demineralization and extraction - Al-Kahtani H.A.; Jaswir I.; Ismail E.A.; Ahmed M.A.; Monsur Hammed A.; Olorunnisola S.; Octavianti F. (Taylor and Francis Inc., 2024)
Indexed by SCOPUS